Burden of pertussis in infants in the Eastern Mediterranean Region and the impact of maternal vaccination: a systematic review - Randa K. Saad; Yousef Khader; Flor M. Munoz; Faris Lami; Ezzeddine Mohsni; Nadine Haddad (BMC Public Health)
Abstract Background Despite vaccine availability, Pertussis remains a global public health challenge, especially among infants. The Eastern Mediterranean Region (EMR) presents a diverse epidemiological landscape with varying vaccination coverages and healthcare infrastructures. This systematic review aimed to assess the burden of pertussis in infants < 1 year of age in the EMR and evaluate the use and impact of pertussis vaccination during pregnancy. Methods Following PRISMA guidelines, we conducted a systematic search of Scopus, Embase, CINAHL Ultimate, and PubMed from inception until April 30, 2024. Studies included reported on pertussis burden in infants or maternal vaccination. Data extraction and quality assessment were performed in duplicate, focusing on incidence, age distribution, disease severity, and vaccination uptake and impact when data were available. Results Thirty-six studies were included, the majority from Iran (N = 11), Morocco (N = 5), Tunisia (N = 5), and Oman (N = 3), with underrepresentation of other EMR countries. The incidence of PCR-confirmed pertussis among children with suspected pertussis varied significantly, from 6.7% to 8.9% (Morocco 2018–2019) to 50.4% and 51.6% (Palestine 2004–2008) among children < 12 and < 6 months, respectively, and between 16.3% (Tunisia 2007–2016) to 73.0% (Morocco 2013–2015) in children < 2 months. Age distribution data indicated the highest burden was in infants < 2 months regardless of the population studied. High hospitalization rates and severe complications, including seizures and the need for ventilatory support, were frequently reported in infants < 6 months of age. Only one study from Saudi Arabia addressed maternal pertussis vaccination, reflecting low vaccine uptake and awareness among pregnant women. Conclusions This review underscores the substantial burden of pertussis among infants in the EMR and the lack of data on maternal immunization. The findings emphasize the need for enhanced surveillance and targeted public health interventions to reduce disease incidence. Future research should prioritize underrepresented countries to ensure comprehensive data for informed public health strategies. Trial registration PROSPERO (CRD42024573471)